Tourism Destination Marketing: A Case Study of Puri Sea Beach in Odisha, India - MOHANTY, P.P.; ROUT, H.B. (Journal of Environmental Management and Tourism, 2016)
The greatest attraction of Odisha is the Puri sea beach which is acclaimed to be one of the best sea beaches of the world. Puri is one of the most marvelous city of Odisha which lies in the seashore of Bay of Bengal. The Puri sea beach is dotted with wonderful temples, ponds, lakes, heritage palaces, culture, art and crafts and many more. The magnificent and culturally enriched city has bountiful of natural as well as architectural beauty and wonders that always allures the tourists and travelers from all corners of the world. In lieu of many future prospect and potentialities, the tourism of this place did not prosper to the larger extent. It can be rightly said that this particular destination is somehow neglected by Odisha people and the panoramic beauty of this place is yet to be explored properly by domestic and international tourists. The purpose of this research was to discuss the present scenario of Puri sea beach including all tourism facilities, expectations, and demand of the tourist’s concernedness. Moreover, the significance of destination marketing of Puri sea beach as a tourists’ destination and what kinds of marketing methods and strategy can be used to attract more tourists to Puri sea beach, was also discussed here.
Keywords: Odisha; brand; destination; marketing strategy